PRODUCTION OF ARTISANAL CACHAÇA - de Oliveira, Lucas de Oliveira; Ferrarezi Junior, Edemar (Revista Interface Tecnológica, 2022)
As seen in historical books that portray the evolution of a drink ingested by native peoples and slaves, in which it was a drink without knowledge, cachaça appeared in Brazil, however in the degree of knowledge that the drink gained before the people, it was gaining space on gentlemen’s tables because it is a more available drink. Cachaça has a great role in the history of Brazil and over the years it has gained more space. The purpose of this work is to show artisanal cachaça, presenting its evolution over the years, as it is a drink that is present in the history of Brazil, since its colonial period, and there are several alternatives until the distilled drink appears, which is one of the drinks most consumed by Brazilians and being more sought after outside the country. The guideline of this work was elaborated through bibliographical research, supported by works that cover the chosen theme, theoretical research, official websites and scientific articles.